Molecular characterization of infectious bursal disease virus (IBDV) isolated in Argentina indicates a regional lineage - Vera, Federico Sebastian; Craig, María Isabel; Olivera, Valeria Soledad; Rojas, María Florencia; Konig, Guido Alberto; Pereda, Ariel Julian; Vagnozzi, Ariel Eduardo (2018)
In Argentina, classical vaccines are used to control infectious bursal disease virus (IBDV); however, outbreaks of IBDV are frequently observed. This could be due to failures in the vaccination programs or to the emergence of new strains, which would be able to break through the protection given by vaccines. Hence, genetic characterization of the viruses responsible for the outbreaks that occurred in recent years is crucial for the evaluation of the control programs and the understanding of the epidemiology and evolution of IBDV. In this study, we characterized 51 field samples collected in Argentina (previously identified as IBDV positive) through the analysis of previously identified apomorphic sequences. Phylogenetic analysis of regVP2 showed that 42 samples formed a unique cluster (Argentinean lineage), seven samples were typical classical strains (one of them was a vaccine strain), and two belonged to the very virulent lineage (vvIBDV). Interestingly, when the analysis was performed on the regVP1 sequences, the field samples segregated similarly to regVP2; thus, we observed no evidence of a reassortment event in the Argentinean samples. Amino acid sequence analysis of regVP2 showed a particular pattern of residues in the Argentinean lineage, particularly the presence of T272, P289 and F296, which had not been reported before as signature sequences for any IBDV phenotype. Notably, the residue S254, characteristic of the antigenic variant, was not present in any of the Argentinean samples.